PENGEMBANGAN KETERAMPILAN MENGHADAPI SITUASI DARURAT DAN MENCEGAH KENAKALAN DI KALANGAN MAHASISWA - Nurhemah, Neng; Rosmiati, Yatti; Janvierna Lusie Putri, Mas Fierna (LPPM Universitas Sangga Buana, 2025)
University students are a vulnerable group when facing emergencies and engaging in delinquent behaviors, often due to a lack of skills in managing environmental pressures. This issue is the main focus of a Community Service Program (PkM) implemented at Pamulang University. The objective of this program is to enhance students' preparedness for emergency situations and prevent their involvement in delinquent behaviors. The target of this program was 50 students from Pamulang University. The program activities included interactive lectures, case studies, practical training for handling emergencies (such as fires, accidents, and criminal acts), and educational sessions on the causes, impacts, and prevention of juvenile delinquency. The results indicated an 80% improvement in students’ knowledge of emergency handling strategies, a 75% increase in practical skills, and a 65% reduction in the potential involvement in delinquency, based on pre- and post-test evaluations. In conclusion, this PkM program effectively enhances students’ preparedness for emergency situations and provides a better understanding of juvenile delinquency prevention efforts. The program is expected to serve as a model for character development in higher education, fostering students who are prepared, responsive, and socially responsible.